Gendered Urban Violence Among Brazilians : Painful Truths From Rio De Janeiro and London - Cathy McIlwaine; Paul Heritage; Miriam Krenzinger Azambuja; Moniza Rizzini Ansari; Eliana Sousa Silva; Yara Evans (Manchester University Press, 2024)
This book aims to examine the nature of and resistance to gendered urban violence among Brazilian women in London and in the favelas of Maré, Rio de Janeiro. Drawing on the conceptualisation of translocational gendered urban violence framework, it highlights the importance of examining direct forms of gender-based violence across private, public and transnational spheres as interlinked with structural, symbolic and infrastructural violence. The book also explores the embodied and spatialised nature of gendered urban violence, explored through artistic engagements and arts-based methods. In developing a translocational feminist tracing methodological and epistemological approach across the social sciences and the arts, the book argues for the importance of a collaborative approach among academic, civil society organisations, artists and creative researchers with a view to engendering empathetic transformation to address gendered urban violence in the long-term.